Background signals in stimulated Raman scattering microscopy and current solutions to avoid them. Issue 1 (31st December 2023) - Genchi, Luca; Laptenok, Sergey P.; Liberale, Carlo
ABSTRACT: Stimulated Raman scattering (SRS) microscopy has gained popularity in recent years due to its linearity to molecule concentration and laser intensity, and to the lack of the nonresonant background that affects its analogous technique, coherent anti-Stokes Raman scattering. However, SRS is not a background-free technique. In fact, there are other optical processes – nonlinear transient scattering and nonlinear transient absorption – that can be detrimental to the contrast and sensitivity of SRS microscopy. In this review, we provide a description of these competing optical processes and present an up-to-date description of current solutions to minimize their effect on SRS measurements. Graphical Abstract: uf0001